Morphology and dimensions of maxillary dental arch in individuals with bilateral cleft lip and palate: evaluation of the influence of primary plastic surgeries - Huayta Aguirre, Ingrid Ivanna (2019)
Bilateral cleft lip and palate (BCLP) can be considered the most severe of cleft lip and palate (CLP) anomalies, due to its esthetic and functional implications. The rehabilitation process is arduous from the beginning because of the marked forward premaxilla projection, which is an important characteristic in this type of CLP and increases the difficulty of initial surgical procedures. These plastic surgeries can negatively influence the maxillary development. The objective of this study was to evaluate the influence of plastic surgeries (lip and palate repair) on the development of maxillary segments in children with BCLP. This longitudinal observational retrospective study was conducted at the Hospital for Rehabilitation of Craniofacial Anomalies of University of Sao Paulo, Bauru, Brazil. Dental casts were obtained in two times, the first before primary plastic surgeries (T0) and the second after 5 years of age (T1) in the same individual. The scanned dental models were analyzed on a software to obtain angular and linear measurements. The t-test, Mann-Whitney test and Spearman´s correlation test were applied for statistical analysis. There were significant changes in dental casts in T1 that evidenced the influence of primary plastic surgeries on maxillary development. The most affected structure was the premaxilla, and its retropositioning worsened the anterior dental arch collapse. The maxillary and premaxillary development are highly susceptible to primary surgeries performed on the individual with BCLP.